The Effectiveness of Wordwall on English Tense Mastery and Learning Motivation - Robertus Ruben; Sultan Baa; Abdullah Abdullah (Newinera Publisher, 2026)
This study investigates the effectiveness of Digital Game-Based Learning (DGBL) in improving students’ grammar mastery in English as a Foreign Language (EFL) context. The integration of digital games into language instruction has gained increasing attention as an innovative pedagogical approach that promotes interactive, engaging, and student-centered learning environments. This research employed a quasi-experimental design with a non-equivalent control group involving two intact classes of tenth-grade students. The experimental group received grammar instruction through Wordwall-based DGBL activities, while the control group was taught using conventional teaching methods. Data were collected through pre-tests and post-tests to measure students’ grammar achievement. The results were analyzed using statistical procedures to determine the effectiveness of the treatment. The findings indicate that students in the experimental group showed significantly higher improvement in grammar performance compared to those in the control group. This suggests that the implementation of DGBL, particularly through Wordwall, can effectively enhance students’ understanding and retention of grammatical structures. Furthermore, the study highlights that DGBL not only improves cognitive outcomes but also increases students’ motivation and engagement in learning English. Therefore, it is recommended that English teachers integrate digital game-based platforms into classroom instruction to create more interactive and meaningful learning experiences.